A systematic review: polyphenol’s effect on food allergy via microbiome modulation - Rana, Tekan Singh; Bansode, Rishipal Rastrapal; Rana, Jenny Pakhrin; Williams, Leonard L. (Frontiers in Microbiology, 2025)
IntroductionFood allergy is an increasing health concern worldwide. Microbes, food allergies, and polyphenols are found to be interrelated. However, studies relating polyphenols’ effect on food allergy via microbiome modulation are scarce, and there is a lack of common signature microbiome modulation patterns. Thus, this review aims to summarize the effect of polyphenols on food allergy via microbiome modulation.MethodsResearch articles were searched from Scopus, PubMed, ScienceDirect, and Web of Science database. The in vivo and in vitro studies were assessed via SYRCLE risk of bias and modified CONSORT checklist, respectively. The population characteristics and experimental details were extracted, and the data were synthesized narratively.ResultsThe included studies were free of selective reporting of results. The allergy of egg (ovalbumin), milk (𝛽-lactoglobulin), soybean (𝛽-conglycinin), and shrimp allergy contributed to 54%, 23%, 15%, and 8% of the total included studies, respectively. The used compounds were a different source or types of polyphenols such as cocoa, cyanidin-3-O-glucoside (C3G), avenanthramide's (AVA), rosmarinic acid (RA), neohesperidin, and fermented apple juice for egg allergy, luteolin, and green tea polyphenol (GTP) for soybean allergy, and flavonoids (Luteolin, myricetin and hyperoside), ferulic acid, and luteolin for milk allergy. Allergies of milk, egg, wheat, and shrimp occurred with the reduction of Lactobacillus, Alistipes, Odaribactor, Akkermansia, Bacteroides, and Lachnospiraceae_NK4A136_group and an increase of Prevotella, Alloprevotella, Faecalibaculum, Helicobactor, Blautia, Clostridium, and Staphylococcus. The polyphenols modulated these microbes in order to attenuate the food allergies.DiscussionThe types of polyphenols, food allergies, animal model used, and taxonomic resolution of the microbiome studies lead to variation in the results. Thus, by increasing the studies on effect of polyphenols on individual food allergies, and combining with higher taxonomic resolution techniques such as shotgun metagenomics along with metabolomics would increase reliability of the results of the future studies.